"I am an atypical mother": Motherhood and maternal language in Giovanna Cristina Vivinetto's poetry. (May 2021) - Cannamela, Danila
In her debut book Dolore minimo, Giovanna Cristina Vivinetto engages in a reflection on motherhood to recount an autobiographical story of gender self-determination and male to female transition. This article explores Vivinetto's poetry as the retelling of transformative moments in two mother–daughter relationships, which generate a reshaping of life and language. In the book, these two storylines intersect, blur, and even overlap, creating a poetic discourse in which the maternal acts simultaneously as powerful catalyzer and producer of meanings. In discussing how, in Dolore minimo, the relationship of two atypical mothers becomes the creative site of a new possible symbolic order, my analysis engages an atypical approach: it reads Vivinetto's queer representation of motherhood via the theorization developed by the women of Diotima—including, in particular, Luisa Muraro, Chiara Zamboni, Diana Sartori, and Ida Dominijanni. These feminist thinkers have been generally criticized for reinforcing binary understandings of sex and gender, based on an essentialist view of the category of woman. Yet, what if the feminism forwarded by Diotima, by positioning the feminine as a creative producer and first-person narrator of change, could still offer a productive avenue for dialogue? The article begins with a discussion of Diotima's key theorizations, which lays the groundwork for interpreting the maternal poetics of Dolore minimo . The subsequent sections examine in more depth how Vivinetto's poetry has reinvented the figure of the mother as a teacher and learner of new words, and how, through this reinvention, she has crafted a maternal language that knits together new relations of contiguity and change. Ultimately, by redeploying the figure of the mother beyond cisgender norms, Vivinetto's poetry is revealing the inexhaustible vitality of this character.